Correlations between circulating methylmalonic acid levels and all-cause and cause-specific mortality among patients with diabetes - Wang, Jiao; Tang, Yunliang; Liu, Ying; Cai, Wei; Xu, Jixiong (Frontiers in Nutrition, 2022)
Aims: Evidence regarding serum methylmalonic acid (MMA) levels and mortality in individuals with diabetes is limited. This study aimed to evaluate the correlation between MMA and all-cause and cause-specific deaths in patients with diabetes. Methods: This is a population-based cohort study based on data from both the National Health and Nutrition Examination Survey and National Death Index from 1999 to 2014. We assessed the association of serum MMA concentrations with mortality using Cox proportional hazard models after adjusting for lifestyle, demographic factors, and comorbidities. Results: Among the 3,097 participants, 843 mortalities occurred during a median follow-up of 4.42 years. There were 242 deaths due to cardiovascular disease (CVD) and 131 cancer-associated deaths. After multivariate adjustment, elevated serum MMA levels were markedly correlated with a high risk of all-cause, CVD-, and cancer-related deaths. Each one-unit increase in the natural log-transformed MMA level correlated with increased risk of all-cause mortality (2.652 times), CVD mortality risk (3.153 times), and cancer-related mortality risk (4.514). Hazard ratios (95% confidence intervals) after comparing participants with MMA <120 nmol/L and ≥250 nmol/L were 2.177 (1.421-3.336) for all-cause mortality, 3.560 (1.809-7.004) for CVD mortality, and 4.244 (1.537-11.721) for cancer mortality. Conclusions: Higher serum MMA levels were significantly associated with lower all-cause, CVD, and cancer mortality. These findings suggest that maintaining lower MMA status may lower mortality risk in individuals with diabetes.